Pengetahuan Ibu Hamil tentang Gizi Masa Kehamilan sebagai Upaya Pencegahan Stunting - Chori Elsera; Soniya, Soniya; Marwanti, Marwanti; Permatasari, Devi; Hamranani, Sri Sat Titi (Universitas Muhammadiyah Klaten, 2023)
In recent years, stunting has still been a health problem that has been highlighted and received priority for immediate treatment. Various factors influence the increase in the incidence of stunting, starting from internal and external factors. Knowledge is one of the internal factors that can influence the increase in stunting incidents. This research was conducted with the aim of knowing the level of knowledge of pregnant women about nutrition during pregnancy in an effort to prevent stunting. This research method is quantitative with a cross sectional approach on a sample of 60 pregnant women using a simple random sampling technique. The results of this research are that the majority of pregnant women have insufficient knowledge (41.7%) about the nutrition of pregnant women in the context of preventing stunting. The conclusion of this research is that the majority of pregnant women have insufficient knowledge about the nutrition of pregnant women in efforts to prevent stunting